IBD and Bile Acid Absorption: Focus on Pre-clinical and Clinical Observations - Fitzpatrick, Leo R.; Jenabzadeh, Paniz (Frontiers in Physiology, 2020)
Inflammatory bowel disease (IBD) causes chronic inflammation affecting the GI tract, It is classified as consisting of Crohn’s Disease (CD) and Ulcerative C olitis (UC). Bile Acid absorption is altered in both pre-clinical models of Inflammatory Bowel Disease (IB) and in human IBD. The bile acid transporter, apical sodium dependent bile acid transporter (ASBT) showed decreased expression in rats with TNBS colitis. Decreased ASBT expression has also been described in murine, canine and rabbit models of intestinal inflammation. Human IBD studies have shown that an inflamed ileum can interrupt enterohepatic recirculation of bile acid, which could be due to inflammatory cytokine induced repression of the ASBT promoter. There are different hypotheses as to why ASBT is downregulated during CD. In addition, one study has demonstrated the beneficial effect of a glucocorticoid on ASBT expression when treating IBD. Our aim in this review paper was to systematically review various aspects of bile acid malabsorption in animal models of IBD, as well as in IBD.